HGCROC3: the front-end readout ASIC for the CMS High Granularity Calorimeter. (1st March 2022) - Bouyjou, F.; Bombardi, G.; Dulucq, F.; El Berni, A.; Extier, S.; Firlej, M.; Fiutowski, T.; Guilloux, F.; Idzik, M.; De La Taille, C.; Marchioro, A.; Molenda, A.; et al.
Abstract: For the CMS High Granularity Calorimeter (CE), the final version of the 72-channel front-end ASIC (HGCROC3) was submitted in December 2020. HGCROC3 includes low-noise/high-gain preamplifiers/shapers and a 10-bit 40 MHz successive approximation ADC (SAR-ADC) that provide the charge measurement over the linear range of the preamplifier. In the saturation range, a discriminator and a time-to-digital converter (TDC) provide the charge information from the time over threshold (ToT; 200 ns dynamic range, 50 ps binning). A fast discriminator and another TDC provide timing information to 25 ps accuracy. The chip embeds all necessary ancillary services: bandgap circuit, PLL, threshold DACs. We present the experimental results on the latest and final version (HGCROC3) received in April 2021.